Evaluasi Anggaran Belanja Sebagai Alat Pengendali Keuangan Pada Palang Merah Indonesia (PMI) Surabaya - Aminatus Sofia; Achmad Maqsudi (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
This Research Is A Qualitative Study Which Aims To Analyze Deviations Between The Budget Set And The Realization Of Pmi Surabaya's 2018, 2019 And 2020 Budgets. This Research Used 1 (One) Person As An Informant Who Was The Head Of Administration At Pmi Surabaya. Data Collection Methods Use Observation, Interview And Documentation Techniques. The Results Of This Research Show That The Variance Analysis In The Pmi Surabaya Expenditure Budget In 2018 Resulted In Favorable Deviations. In 2019 And 2020 There Were Unfavorable Deviations. This Happens Because There Are Programs That Cannot Be Predicted Considering That Pmi Surabaya Is A Non-Profit Social And Humanitarian Organization That Does Not Solely Pursue Profit And Has The Aim Of Helping To Alleviate The Effects Of Natural And Human-Caused Disasters. So The Budget That Is Set Is One Of The Preparations If These Disasters Occur And Is Often Not In Accordance With The Budget Because We Ourselves Cannot Predict How Many Disasters There Will Be In One Year. However, This Can Be Overcome By Pmi Surabaya Because Pmi Uses Contingency Plans. This Contingency Plan Was Prepared As A Guide For Disaster Management During Emergency Response So That It Takes Place Quickly And Effectively.